Towards a national imagination: the script reform of 1928 in Turkey - Çelik, Yalın Emek. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2006., 2006)
This study is on the Script Reform of 1928 in Turkey. It aims to situate the process of the change from the Arabic Script to the Roman Script within the nationalist transformation projects put into practice in the early republican Turkey. The contemporaneous nationalist discourse and the ideology bore by the governing elite of the time are analyzed with reference to the Script Reform. The consequences of the reform, its impacts on the society and the reflections of the nationalist perception of the time on the social transformations conducted are the main foci of interest for this study. The thesis mainly discusses the intended and/ or unintended rupturing consequences of the reform both in the daily and intellectual life of the early republican period, with a sociological approach.
Keywords: Nationalism -- Turkey.; Turkish language -- Alphabet.